Role of biological rhythms in the performance of physical activity - Sato, T.; Ida, T.; Kojima, M. (The Journal of Physical Fitness and Sports Medicine, 2017)
Most organisms display various periodicities. Periodicity has been observed in humans in association with sleep, body temperature and hormone secretion. The molecular mechanisms involved are being elucidated by the investigation of clock genes in mammals. The relationship between biological rhythms and disease is also being studied. For example, myocardial infarction occurs more frequently in the morning, and disruption of biological rhythm is associated with obesity and diabetes. Some drugs have different medicinal effects depending on the time of dosing. Drug therapy known as chronotherapy, that takes into account the diurnal rhythm found in a given target disease, is being administered in some cases. Moreover, physiological responses and metabolism differ with time. Therefore, understanding the mechanisms underlying biological rhythms could enable the safe and effective performance of physical activity, in addition to potential medical applications. This review article outlines current understandings of biological rhythmicity and explores the relationship between biological rhythms and exercise, training, and sports.